Modelling inflation in the euro area - Eilev S. Jansen (European Central Bank (ECB), 2004)
The paper presents an incomplete competition model (ICM), where inflation is determined jointly with unit labour cost growth. The ICM is estimated on data for the Euro area and evaluated against existing models, i.e. the implicit inflation equation of the Area Wide model (AWM) - cf. Fagan, Henry and Mestre (2001) - and estimated versions of the (single equation) P* model and a hybrid New Keynesian Phillips curve. The evidence from these comparisons does not invite decisive conclusions. There is, however, some support in favour of the (reduced form) AWM inflation equation. It is the only model that encompasses a general unrestricted model and it forecast encompasses the competitors when tested on 20 quarters of one step ahead forecasts.
Keywords: C22; C32; C52; C53; E31; 330; Area Wide model; forecast encompassing; incomplete competition model; inflation; model evaluation; New Keynesian Phillips curve; P*-model